Revitalisasi UMKM Warung Barokah Mbak Ika Melalui Digitalisasi dan Branding untuk Meningkatkan Daya Saing - Yudha, Ahmad Dewa; Putri, Aulia Yogha; Mujiati, Indah; Dewi, Nurma Gupita (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
MSMEs play a crucial role in driving local and national economic growth. However, the majority of Micro, Small, and Medium Enterprises (MSMEs) in rural areas still face various challenges in developing a clear business identity and establishing an effective and competitive digital presence. This community service activity aims to improve the competitiveness of the Warung Barokah Mbak Ika MSME through digitalization and strengthening its branding. The method used was a collaborative and participatory approach between students and MSME partners. The activity stages included initial observation, needs identification, design and creation of branding media, outreach, and evaluation of results. The resulting media included a business logo, printed and digital menus, transaction receipts, table numbers, and location registration on Google Maps. The results of the activity showed an improvement in the business's professional image, ease of customer access to the business location, and positive responses from partners to the provided media. This activity demonstrates that simple branding interventions combined with digitalization strategies can have a significant impact on the development and competitiveness of MSMEs in rural areas. These findings can also be replicated in the context of similar MSMEs in other regions with a tailored approach.